Household Use of Agricultural Chemicals for Soil-Pest Management and Own Labor for Yard Work - Templeton, Scott R.; Zilberman, David; Yoo, Seung Jick; Dabalen, Andrew L. (2012)
In spite of its potential health and environmental risks and contribution to agribusiness, the use of agricultural chemicals for yard care has not been well studied. In our discrete-continuous choice model, estimated with data from a national survey, a household chooses how much money, if any, to initially spend on types of agricultural chemicals and applicators and how much time to subsequently spend on other yard work. Households in big cities or with large gardens are more likely to use organic chemicals. The probability that a household chooses a mix of do-it-yourself and hired applications of synthetic chemicals increases with income, age, and the presence of preschoolers. Among households that apply only synthetic chemicals without hired help, those with young children, with higher incomes, in big cities, and with male heads spend more on the chemicals. The time that such households spend on other yard work increases with expenditures on the chemicals. Cancellation of a pesticide registration might create an extra private cost for households with young children even though the ban might reduce external costs.